Preparation and characterization of room temperature vulcanized silicone rubber using α-amine ketoximesilanes as auto-catalyzed cross-linkers. Issue 44 (18th April 2016) - Zhao, Qian; Liu, Qingyang; Xu, Huihui; Bei, Yiling; Feng, Shengyu
Abstract : A series of α-amine ketoximesilanes were prepared and used as auto-catalyzed cross-linkers in one component room temperature vulcanized (RTV) silicone rubber. Abstract : A series of α-amine ketoximesilanes were prepared and used as auto-catalyzed cross-linkers in one component room temperature vulcanized (RTV) silicone rubber. The synthesized α-amine ketoximesilanes were characterized by Fourier transform infrared spectroscopy (FT-IR) and nuclear magnetic resonance (NMR). Better performances of RTV silicone rubber including tack free time, viscosity, mechanical performances and thermal stability using α-amine ketoximesilanes as cross-linkers were successfully obtained, in comparison to those performances of RTV silicone rubber using commercial methyltris(methylethylketoxime)silane (MOS) as a cross-linker and dibutyltin dilaurate as a catalyst. Further, we applied density function theory (DFT) method to confirm α-amine ketoximesilanes plays a autocatalytic effect in the hydrolytic reaction of α-amine ketoximesilanes with H2 O. The experimental results showed that using α-amine ketoximesilanes as cross-linkers is a practical way to obtain RTV silicone rubber with excellent properties, as well as avoiding using high chemical toxicology of organic metal catalyst in curing system.